Bibliometric analysis of social enterprises: what is their impact on academic production? (Research, Society and Development, 2020)
Social issues have been widely discussed and disseminated by the media in Brazil in recent years. Among the several factors that can explain the appreciation of this issue is the fact that, by assuming a broader responsibility for society as a whole, companies supply community needs that until then were not satisfactorily met by the government. Many experts and practitioners began to believe that only traditional approaches by the government and the nonprofit sector would not be enough to solve social problems. One of the emerging options is a new form of entrepreneurial organization that unites social purpose, associated with the non-profit sector, and economic rationality and market-based approaches associated with for-profit companies, the so-called social enterprise. The objective of this research is to investigate what is the impact of academic production on social enterprises through bibliometrics between 2008 and 2018. The results of bibliometric analysis show that the number of publications grows moderately. In the past few years, only 774 surveys have emerged on social enterprises. Arguably, this may be because research on social enterprises is in its early stages. In addition, knowledge is fragmented because many areas of research mention social enterprises and their characteristics.